The Importance of Digital Literacy in The Era of Society 5.0 - Siahaan, Rina Devi Romauli; Sirait, Gloria (Indo-MathEdu Intellectuals Journal, 2023)
The purpose of writing this article is to understand the importance of digital literacy in the era of society 5.0. The era of society 5.0 is a time when science and technology are used and utilized to facilitate people's lives. The method used in this study is a literature study. The data collection technique in this study is to collect information and data from various library materials such as books, articles, previous research, notes, and journals related to the application of digital literacy in the era of society 5.0. The results of data analysis show that one of the skills needed in the era of society 5.0 is digital literacy skills. Between the era of society 5.0 and digital literacy has the same goal in answering all the challenges of social life and improving decision-making skills The result of this writing is to provide an overview of the concept of the era of society 5.0 and information about the importance of digital literacy in the era of society 5.0.